Analysis and development suggestions of operators in the field of industrial internet identification analysis system - Yufei CUI; Yunyong ZHANG; Di ZHANG; Xiaoxia WANG; Siyu PAN; Kun LI (Dianxin kexue)
With the development of industrial internet technology,5G and edge computing,countries have put forward their own industrial Internet development strategies and construction of industrial Internet platform.Cloud edge collaborative industrial Internet platform is an important part of the development of industrial Internet.The way of industrial Internet cloud edge collaboration was introduced,the problems in the process of cloud edge collaboration were expounded,and practices were taken based on data collaboration and model collaboration.